SELECTIVE OPIOID AGONISTS MODULATE AFFERENT TRANSMISSION IN THE RAT NUCLEUS TRACTUS-SOLITARIUS - RHIM, H; GLAUM, SR; MILLER, RJ (WILLIAMS & WILKINS, 1993)
We examined the effects of agonists at mu, delta and kappa opioid receptors on neurons located in the nucleus tractus solitarius of the rat using whole-cell patch-clamp recordings in brainstem slices. The mu selective opioid agonist DAMGO hyperpolarized most neurons tested. This effect was associated with the activation of a K+-conductance. The effect of DAMGO tended to desensitize and was blocked by naloxone. Dynorphin A also produced this effect. However, the kappa-1-selective opioid agonist U-69593 and two de/ta-selective opioid agonists did not. DAMGO also depressed glutamate-mediated excitatory postsynaptic potentials and GABA-mediated evoked by stimulation of the tractus solitarius. Dynorphin A, U-69593 and delta-opioid agonists also reduced the excitatory postsynaptic potential, although they were less effective than DAMGO. The presynaptic inhibitory effects of DAMGO were also blocked by naloxone, but did not desensitize. These actions may help to explain the ability of opiates to modulate a variety of autonomic reflexes.
Keywords: LOCUS COERULEUS NEURONS; POTASSIUM CONDUCTANCE; MEDULLA-OBLONGATA; OPIATE RECEPTORS; MU-RECEPTORS; NORADRENALINE; CURRENTS; SOMATOSTATIN; NERVE; CATECHOLAMINES